PENGARUH LITERASI KEUANGAN DAN RISK TOLERANCE TERHADAP KEPUTUSAN INVESTASI - Sherli Wahyuni Dwi Afriani; Isnurhadi Isnurhadi; Yuliani Yuliani (J-MACC, 2023)
Investment decision is a person's decision to allocate funds to a certain asset with the aim of obtaining profits in the future. This research aims to examine the influence of financial literacy and risk tolerance on investment decisions. The population in this research are investors in South Sumatra. The sampling technique used is Probability Sampling, namely the slovin formula so that in this study the sample used was 400 respondents. This research was conducted using a quantitative method, the data used was by distributing questionnaires to respondents through online or offline. This research variable consists of X1 financial literacy, X2 risk tolerance, and Y investment decisions. This study uses 2 hypotheses. The data analysis technique uses Structural Equation Modeling (SEM) with the use of SmartPLS software.The results of this research show that financial literacy has a significant effect on investment decisions. Risk tolerance also has a significant effect on financial behavior. Apart from that, financial behavior is able to mediate the relationship between risk tolerance and investment decisions. The better the financial literacy an investor has, the better the quality of the investment decisions they will take. And the higher the risk tolerance level of investors, the higher the preference level of investment decisions that investors are willing to take, so that the higher the level of risk that will be borne.